Hawtrey, Harvard, and the Origins of the Chicago Tradition - Laidler, David (Journal of Political Economy, 1993)
Milton Friedman has claimed that his monetary economics derives from a Chicago Tradition that, in the 1930s, offered a monetary explanation of cyclical fluctuations in general and the Great Depression in particular, an optimistic view of the power of monetary policy, and a case for governing it by rules rather than discretion. It is argued that all the elements of this tradition except the last are to be found in earlier writings of Ralph Hawtrey, Allyn Young, and Lauchlin Currie and that there is much evidence to point to a direct influence running from Hawtrey, through Harvard to Chicago.